Development of interactive ar objects: from code to artistic image - Kalinina, O.; Suprun, O. (ХНЕУ, 2026)
The development of interactive AR objects represents a synthesis of low-level technical procedures and high-level artistic representation.
Keywords: high-level artistic representation; AR objects